Performing Everyday Practices - Carsten Friberg (Ambiances)
In this article the coupling of atmosphere and aesthetic education is proposed as an intersection between awareness of the sensorial and bodily aspects of our everyday practices such and the training of our sensibility towards such sensorial and bodily awareness in specific situations. The concept of atmosphere is introduced to create awareness of how sensorial aspects affect us, and also to explore how perception is about the presence of something. Atmosphere is also a primary concept in aesthetics and relate to a classical tradition of education through sensorial and bodily products. Through a presentation of atmosphere and aesthetic education the intersection between them is suggested as a field for further investigation and also additional training.